INTEGRATION OF VALUE BASED EDUCATION INTO THE FORMAL EDUCATION SYSTEM FOR PEACEFUL SOCIETY: PERSPECTIVE OF BUDDHISM - Bakhati, Pramila (PEOPLE: International Journal of Social Sciences, 2017)
The peaceful mind and environment morals and values are equally important to the life. But all these elements are degrading these days. However, the students should be taught the peace, morals and values in twenty first century education. This can be done through the integration of curriculum between formal and Buddhist education system. Here, the paper analyses the meaning of peace from general view and Buddhist view. It discusses the imbalances in the peace and morals/values through both the general and Buddhist view. Lastly and mainly, it proposes the teaching of peace, morals and values education through the integration of formal education curriculum and Buddhist education. Therefore, incorporating the core human values exemplified in Buddhism into the school curriculum (formal education) aims to first, promote values-based education and, second better equip future generations to live a moral and ethical life which directly contributes for making the Peaceful society.